Tracks from the Past, Connectivity for the Future : Revitalizing Moldova’s Railway Sector - World Bank (World Bank, Washington, DC, 2021)
The railway transport in Moldova plays an important role in the transport market of the country. Historically, railway transported very large volumes of freight and provided important services for passengers in Moldova. Railways lost important volumes of transport during the last two decades for various reasons, culminating with the crisis starting in 2007. The Coronavirus (COVID-19) outbreak has had a major disruptive impact on domestic and international transport and on mobility. The entire transport sector has faced a huge drop in the mobility demand due to many transport customers having been forced to temporarily suspend their activities and international borders having been closed. The current policy note assesses in detail the causes of the decreased market share of railways and will propose solutions for the recovery. This document provides an assessment of the major challenges faced by railway transport in Moldova, formulating a strategy proposal for a profound sector restructuring.